Superovulation and Embryo Yield after GNRH Pretreatment in Crossbred Cows - S. Satheshkumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The effect of GnRH pretreatment on superovulatory response (SOR) and embryo yield in crossbred cattle was studied. Six crossbred cows were subjected to three superovulatory treatments: i. Control: Four day FSH schedule was initiated on Day 10 of the cycle ii. Gn-D8: GnRH was administered on Day 6 and FSH schedule was initiated on Day 8 and iii. GnD10: GnRH was administered on Day 6 and FSH schedule was initiated on Day 10. In control group, the mean SOR was 13.7 + 5.8 CL. In Gn-D8 group, the SOR is inconsistent (5.0 ± 1.7) with recovery of poor quality embryos, which was attributed to significantly higher progesterone concentration on the day of superovulatory oestrus. In Gn-D10 group, SOR (11.0 ± 1.6) and embryo yield were comparable to the control group. Transferable quality embryos were signcantly higher in Gn-D10 group which could be attributed to the follicular maturation under favourable endocrine environment. Thus, GnRH pretreatment in superovulation protocol ensured consistent SOR and increased yield of transferable quality embryos in crossbred cattle.